Peran Musik dalam Ibadah Kristen: Tinjauan Sitematis Terhadap Dimensi Liturgis dan Spritualitas (Systematic Literature Review) - Jumaroh, Ita (Universitas Pahlawan Tuanku Tambusai, 2025)
Music plays a central role in Christian worship, not only as an aesthetic element but also as an important means to deepen the liturgical and spiritual dimensions of the congregation. The background of this study highlights how music facilitates the relationship between the congregation and God, creates a reflective and worshipful atmosphere, and functions theologically to strengthen faith and communal bonds. The purpose of this study is to systematically review the role of music in Christian worship, particularly in the liturgical and spiritual dimensions. The research method used is a Systematic Literature Review (SLR) by identifying, evaluating, and synthesizing relevant previous research. The literature search process was carried out through academic databases such as Google Scholar and DOAJ with keywords such as